EFFECTIVE INVESTMENT IN TECHNOLOGICAL UPDATE - A GUARANTEE OF INNOVATIVE DEVELOPMENT OF THE MACHINERY BUILDING COMPLEX OF UKRAINE - Шитікова, Лариса; alex,; Журило, Максим (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
Modern challenges of the global economy and the rapid development of technologies necessitate constant updating of the material and technical base of enterprises in the machine-building industry. Technological updating is an important factor in ensuring competitiveness, production efficiency and improving product quality. In this context, investment support plays a key role, since the modernization of production facilities, the introduction of innovative technologies and automation of processes require significant financial resources. However, at the current stage of development of the Ukrainian economy, investment support for technological updating of machine-building enterprises faces a number of problems. Among the main obstacles are the lack of internal financial resources, the difficulty of attracting external investments, high credit rates, the instability of the economic environment and insufficient state support for the industry. Solving these issues requires a comprehensive approach, which includes improving financing mechanisms, developing favorable conditions for investors and introducing state incentives. The need to implement a technological update strategy at each enterprise, its possible types and forms are analyzed. It was established that based on the analysis of the current resource and financial condition of the enterprise, the identification of strengths and weaknesses, it is possible to create a structured approach to investment capital aimed at the modernization and scaling of production with the determination of its technological and financial base. The problem of domestic enterprises to carry out technological renewal of production at the expense of borrowed funds or at the expense of state programs aimed at supporting the real sector of the economy was studied. It was established that enterprises are forced to make investment capital investments mainly at the expense of their own funds. The influence of human resources on the effective implementation of technological renewal of the enterprise was analyzed. It was established that the lack of personnel with the necessary qualifications will hinder the implementation of the enterprise's development strategy. The work substantiates that modern strategic management of the entire resource base of the enterprise involves a comprehensive study of the processes that affect the implementation of investment and technological renewal of production in order to achieve competitive advantages and increase profits.